Pengaruh e-CRM terhadap Kualitas Hubungan dan Hasil dengan Atribut Layanan dan Pemulihan Layanan sebagai Variabel Mediasi - Apriyanti, Rini; Rohman, Fatchur; Indrawati, Nur Khusniyah (University of Merdeka Malang, 2021)
This research is expected to find out more about the effect of e-Customer Relationship Management (e-CRM) on relationship quality and outcomes by using service attributes and service recovery as a mediating variable for customers of PT BCA Tbk, The Main Branch of Malang. This study uses a quantitative approach by explanatory research. An online survey method which was conducted on 132 priority customer of PT BCA Tbk The Main Branch of Malang. The analytical method uses SEM-PLS. This research shows that the quality of the relationship results is significantly influenced by e-CRM, and is also significantly and directly influenced by service attributes and service recovery. Each service attributes and service recovery were found to act as mediators in this study, namely partially mediating e-CRM on relationship quality and results. The results also convey that e-CRM can directly and significantly influence each service attribute and service recovery. It's miles hoped this research can assist practitioners in improving the relationship quality and outcomes of the company and customer relationships with e-CRM, through service attributes and service recovery.